A differential game model for a two-way referral mechanism between hospitals and the community in China. (2nd September 2022) - Li, Gan; Han, Chuanfeng; Yu, Zibo; Liu, Pihui
A two-way referral system is an important attempt to address the difficulty and expense of medical services in China and, thus, may improve the efficiency of the entire medical system. Most of the current research focuses on the practical experience of two-way referral, and few quantitative studies have been carried out on the decision-making behaviour of referral subjects. Considering the profit-seeking nature of medical institutions, this paper proposes a differential game model with the Community Healthcare System (CHS) and large hospitals, and compares the impact of two-way referral on the income of each medical institution. The evolutionary process is simulated with MATLAB. The results show that the two-way referral system could greatly increase the revenue and enthusiasm of CHSs. However, this system has harmed the interests of large hospitals to a certain extent. For the implementation of the two-way referral system, the government should reorganise urban health resources so that medical institutions are more inclined to make referral decisions and fundamentally eliminate barriers to profit.